Performance of the fixed pressure valve with antisiphon device SPHERA® in the treatment of normal pressure hydrocephalus and prevention of overdrainage - Pereira, Renan M.; Suguimoto, Mariane T.; Oliveira, Matheus F.; Tornai, Juliana B.; Amaral, Ricardo A.; Teixeira, Manoel Jacobsen; Pinto, Fernando Campos Gomes (Arquivos de Neuro-Psiquiatria, 2016)
Normal pressure hydrocephalus (NPH) is characterized by the triad of gait apraxia, dementia and urinary incontinence associated with ventriculomegaly and normal pressure of cerebrospinal fluid. Treatment is accomplished through the implantation of a ventricular shunt (VPS), however some complications are still frequent, like overdrainage due to siphon effect. This study analyses the performance of a valve with anti-siphon device (SPHERA®) in the treatment of patients with NPH and compares it with another group of patients with NPH who underwent the same procedure without anti-siphon mechanism (PS Medical® valve). 30 patients were consecutively enrolled in two groups with 15 patients each and followed clinically and radiologically for 1 year. Patients submitted to VPS with SPHERA® valve had the same clinical improvement as patients submitted to VPS with PS Medical®. However, complications and symptomatology due to overdrainage were significantly lower in SPHERA® group, suggesting it as a safe tool to treat NPH.
Keywords: normal pressure hydrocephalus; cerebrospinal fluid shunt technology; complications